2019
DOI: 10.2478/amcs-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

LMI–Based Robust Control of Uncertain Nonlinear Systems via Polytopes of Polynomials

Abstract: This investigation is concerned with robust analysis and control of uncertain nonlinear systems with parametric uncertainties. In contrast to the methodologies from the field of linear parameter varying systems, which employ convex structures of the state space representation in order to perform analysis and design, the proposed approach makes use of a polytopic form of a generalisation of the characteristic polynomial, which proves to outperform former results on the subject. Moreover, the derived conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Methodology: The proposal is based on an exact convex rewriting of the uncertain nonlinear system over a compact set 38 and a formulation of the exact discretization as an Euler discrete approximation with norm‐bounded uncertainties; knowledge of the exact discretization, which is not obtainable in general, is thus not required. A robust digital controller is designed in the spirit of Reference 33 for the aforementioned formulation; it is shown that its sampled‐data implementation robustly stabilizes the continuous uncertain nonlinear system.…”
Section: Introductionmentioning
confidence: 99%
“…Methodology: The proposal is based on an exact convex rewriting of the uncertain nonlinear system over a compact set 38 and a formulation of the exact discretization as an Euler discrete approximation with norm‐bounded uncertainties; knowledge of the exact discretization, which is not obtainable in general, is thus not required. A robust digital controller is designed in the spirit of Reference 33 for the aforementioned formulation; it is shown that its sampled‐data implementation robustly stabilizes the continuous uncertain nonlinear system.…”
Section: Introductionmentioning
confidence: 99%